Mapping academic production on environmental management and traditional communities (Research, Society and Development, 2021)
The present article aims to map the academic production relating environmental management and traditional communities through bibliometric analysis. In order to do so we compiled scientific articles published between the years 2007 and 2021 using the Web of science database and the VOSviewer software that allows for authors, coauthors, countries, organizations and key-words search. Traditional communities are mostly comprised by native people that exist  preserving both original territory and culture. Their resistance to centuries of colonization is possible by means of their unique relationship with their surrounding environment as for them nature is extremely valuable beyond economical factors. Nature provides for them physically but also to their beliefs and culture. For that reason, international organizations like the International Labour Organization and the World bank consider the preservation of such communities fundamental for the socio environmental development since their knowledge of nature can be useful for the development of new eco friendly ways of using natural resources. On that subject, our research identified many papers on environmental management and traditional communities that revealed these communities take the lead on environmentally engaged management, specially in researches focused on sustainable development, biodiversity maintenance and traditional knowledge applied.